Clickbait on Indonesia Online Media - Yayat D. Hadiyat (Jurnal Pekommas, 2019)
Information and Communication Technology (ICT) brings changes in various fields including influencing the media landscape with the development of online media and the way people consume media online. This change makes the media must be able to attract online media readers using the clickbait article title. Therefore, this study is to find out how online media packages clickbait article. This research is a qualitative research method with the object of this research are clickbait titles in Indonesian online media that are selected based on certain criteria that are in accordance with the research problem. The results of this study indicate that, in general, the use of clickbait article titles is widely used by online media to attract the interest of readers by disturbing the curiosity that arises due to the information gap between what the reader knows and what the reader wants to know. The titles of many clickbait articles focus on the subject of celebrities, rumors, and fictitious accounts and some don't even have news value. The main purpose of using the clickbait article title is to direct online media users to increase visit statistics which are then used to earn revenue through advertising.